PENDAMPINGAN PENELAAHAN ARTIKEL-ARTIKEL DALAM BERKALA ILMIAH MENUJU AKREDITASI SINTA - Setyawan, Ignatius Roni; Hapsari, Claudia Gita; Situmorang, Novrida Fransisca (Jurnal Serina Abdimas, 2023)
Background. Recognizing the importance of scientific journals as pillars of the solidity of study programs in responding to the demands of the tridharma role of higher education, from December 2022 to February 2023 the ABDIMAS team has conducted intensive discussions about the management of scientific journals with one PTS in Yogyakarta which happens to have two scientific journals in accounting and management that has not been accredited by SINTA even though it has been operating for a long time. Furthermore, through several online meetings, it was finally agreed upon a mentoring activity for the two scientific journals which would explore the role of external review partners which had so far been on the list of reviewer names on the journal's website, but had not been utilized optimally to conduct a real review process. Implementation Method Before the activities were carried out online on March 18, 2023, the ABDIMAS team was also involved in reviewing several articles in several edition categories and found the result that many articles needed to maximize content, style, and reference management. The results of the activity The output of the review process was also presented during the ABDIMAS activity with zoom on Saturday 18 March 2023. These results received a positive response from the journal editor at FEB UKDW and the lecturers who acted as reviewers. Another positive result is the presentation about being a good and friendly editor from Prof. Lucey (2013), management of the PBFJ journal from Prof. Faff (2022), and deepening Mendeley's material to improve the quality of reference management and citation of scientific articles. Conclusion The ABDIMAS activity has received a good reception from JRAK and JRMB so that it is considered to be sufficient provision for the process of advancing SINTA 3 accreditation in June 2023 through the ARJUNA application media. Latar Belakang. Menyadari pentingnya jurnal ilmiah sebagai pilar kekokohan program studi dalam menjawab tuntutan peran tridharma perguruan tinggi, maka sejak bulan Desember 2022 hingga Februari 2023 tim ABDIMAS telah melakukan diskusi intensif tentang tata kelola jurnal ilmiah dengan satu PTS di Yogyakarta yang kebetulan memiliki dua jurnal ilmiah bidang akuntansi dan manajemen yang belum terakreditasi SINTA walauapun sudah beroperasi lama. Selanjutnya, melalui beberapa kali pertemuan secara daring akhirnya disepakati suatu kegiatan pendampingan bagi kedua jurnal ilmiah yang akan mengupas peran mitra bestari eksternal yang selama ini sudah ada dalam daftar nama reviewer di website jurnal, namun belum dimanfaatkan secara optimal untuk melakukan proses review secara nyata. Metode Pelaksanaan Sebelum kegiatan yang dilakukan secara daring tanggal 18 Maret 2023, maka tim ABDIMAS juga terlibat melakukan review pada beberapa artikel dalam beberapa kategori edisi dan menemukan hasil bahwa banyak artikel yang perlu dimaksimumkan isi, gaya selingkung, dah manajemen referensinya. Hasil Kegiatan Luaran proses review juga disampaikan pada saat kegiatan ABDIMAS dengan zoom pada Sabtu 18 maret 2023. Hasil ini mendapat sambutan positif dari editor jurnal di FEB UKDW serta para dosen yang bertindak sebagai reviewer. Hasil positif lainnya adalah penyampaian paparan tentang menjadi editor yang baik dan bersahabat dari Prof. Lucey (2013), tatakelola jurnal PBFJ dari Prof. Faff (2022), dan pendalaman materi mendeley untuk meningkatkan kualitas manajemen referensi dan sitasi artikel ilmiah. Kesimpulan Kegiatan ABDIMAS telah mendapat sambutan baik dari pihak JRAK dan JRMB sehingga dinilai menjadi bekal cukup untuk proses maju akreditasi SINTA 3 di Juni 2023 melalui media aplikasi ARJUNA.